Current investigations on tritiated dust and its impact on tokamak safety. (22nd July 2019) - Grisolia, C.; Gensdarmes, F.; Peillon, S.; Dougniaux, G.; Bernard, E.; Autricque, A.; Pieters, G.; Rousseau, B.; Feuillastre, S.; Garcia-Argote, S.; Carvalho, O.; Malard, V.; et al.
Abstract: During International Thermonuclear Experimental Reactor operation, due to plasma–wall interaction, particles/dust will be created in sizes ranging from nanometers to tens of microns. The dust properties, especially their ability to be covered by a thin oxide electrostatic insulating layer, and surface topology deeply affect their tritium inventory. Consequently, physico-chemical properties specific to tritiated tungsten particles and consequence on particle behavior in the facility and environment must be carefully assessed. For size-relevant tungsten particles, the measured tritium inventory is ~10 GBq g −1 . However, it varies with the particle specific surface area. Due to tritium beta decay and the oxide-insulating layer, dust exhibits a positive electrostatic self-charging. For a 5 µ m particle in diameter with a 10 GBq g −1 tritium inventory, self-charging rate could lead to 5.5 10 4 elementary electric charges per day. These electrostatic properties could change the adhesion of dust on walls. In the case of a single particle, the adhesion will be reinforced due to image and dielectric forces. However, if the tritiated particle is part of an aggregate, the adhesion remains unknown. Due to the limited free path of the β emission in material, the tritium inventory carried by airborne particles cannot be measured in real time by conventional continuous radioactive aerosols monitors, and a new measurement strategy is needed for atmospheric surveillance in the workplace and of facility exhaust. Toxicity studies dealing with exposure to untritiated/tritiated tungsten particles of 100 nm have been undertaken. It was shown that these particles are rapidly dissolved in biologic media. Finally, after collection, dust must be confined to avoid its spreading into the environment. Different technical solutions are presented in this paper.